STRATEGI FUNGSIONAL PADA PENINGKATAN PENGGUNAAN GEDUNG GRHA WIKSA PRANITI BANDUNG - Nurlaila Fadjarwati; Gia Yesyah Asih Pratami (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2014)
The purpose of this research with title “Functional Strategies to Increase the Use of Grha Wiksa Praniti Building, Bandung” is to analyze functional strategies to increase the use of Grha Wiksa Praniti building. Used method in this research is descriptive method. Analysis of data using descriptive analysis. The result from this research is in the strategic research and development using housing innovation and technology. Production (operation) strategy is building development with environmentally friendly concept. Marketing strategy consists of market selection, product, price, distribution system/place, and promotion. Market selection is for Public Works Ministry with the main target areas of Jakarta and West Java, the product is still in good condition, for a price is not charged because in assets use suit with the main task and function, the distribution system is not needed to reach the site, promotion using brochure, using website and increase the socialization. Financial strategy performed with alocate operational budget and special maintain for Grha Wiksa Praniti building.